SUSTAINABILITY OF LEXICON IN BATU BARA MALAY LANGUAGE - Harry Sambayu (Universitas Asahan, 2019)
Lexicon as a small component in a language has a big point in identify the sustainability of language among its language community. By observing the different level of language use in their language user we will able to measure the sustainability of a language. Migration, intercultural marriage and natural factors are some factors that affect the sustainability of the lexicon. This study include in a qualitative research. The aim of this study is to investigate the level of sustainable of lexicon among Batu Bara Malay language users. Its result there are some indications that emphasis that the Batu Bara Malay lexicon are in danger position. It should be save by language revitalization program by the government in this region. Keyword : Lexicon, Batu Bara Malay, Sustainabiity